Reversible Calcium-Regulated Stopcocks in Legume Sieve Tubes - Knoblauch, Michael (American Society of Plant Biologists, 2001)
Sieve tubes of legumes (Fabaceae) contain characteristic P-protein crystalloids with controversial function. We studied their behavior by conventional light, electron, and confocal laser scanning microscopy. In situ, crystalloids are able to undergo rapid (<1 sec) and reversible conversions from the condensed resting state into a dispersed state, in which they occlude the sieve tubes. Crystalloid dispersal is triggered by plasma membrane leakage induced by mechanical injury or permeabilizing substances. Similarly, abrupt turgor changes imposed by osmotic shock cause crystalloid dispersal. Because chelators generally prevent the response, divalent cations appear to be the decisive factor in crystalloid expansion. Cycling between dispersal and condensation can be induced in opened cells by repetitive exchange of bathing media containing either Ca(2+) or chelators. Sr(2+) and Ba(2+), but not Mg(2+), are equally active. In conclusion, the fabacean P-protein crystalloids represent a novel class of mechanically active proteinaceous structures, which provide an efficient mechanism with which to control sieve tube conductivity.